2012
DOI: 10.1371/journal.pone.0052730
|View full text |Cite|
|
Sign up to set email alerts
|

Pyrosequencing Investigation into the Bacterial Community in Permafrost Soils along the China-Russia Crude Oil Pipeline (CRCOP)

Abstract: The China-Russia Crude Oil Pipeline (CRCOP) goes through 441 km permafrost soils in northeastern China. The bioremediation in case of oil spills is a major concern. So far, little is known about the indigenous bacteria inhabiting in the permafrost soils along the pipeline. A pilot 454 pyrosequencing analysis on the communities from four selected sites which possess high environment risk along the CRCOP is herein presented. The results reveal an immense bacterial diversity than previously anticipated. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 43 publications
(56 reference statements)
5
39
1
Order By: Relevance
“…The available nitrogen showed a positive correlation to Bacteroidetes, Planctomycetes, Firmicutes, and Crenarchaeota, while it had the negative correlation to Proteobacteria and Gemmatimonadetes. The most dominant bacteria in the greenhouse-based vegetable land were Proteobacteria, which was in agreement with a summary report for several soils [29]. The members of Proteobacteria cover enormous morphological and metabolic diversity, playing a crucial role in the global carbon, nitrogen and sulphur cycles [30].…”
Section: Bacterial Community Compositionsupporting
confidence: 88%
See 1 more Smart Citation
“…The available nitrogen showed a positive correlation to Bacteroidetes, Planctomycetes, Firmicutes, and Crenarchaeota, while it had the negative correlation to Proteobacteria and Gemmatimonadetes. The most dominant bacteria in the greenhouse-based vegetable land were Proteobacteria, which was in agreement with a summary report for several soils [29]. The members of Proteobacteria cover enormous morphological and metabolic diversity, playing a crucial role in the global carbon, nitrogen and sulphur cycles [30].…”
Section: Bacterial Community Compositionsupporting
confidence: 88%
“…Among Proteobacteria, the relative abundance of Gamma-, Alpha-, Beta-, and Delta-subdivisions averaged to 38.73 % (2489 OTUs), 26.51 % (1745 OTUs), 21.23 % (1398 OTUs), and 13.42 % (883 OTUs), respectively. However, the Epsilonproteobacteria only accounted for 0.002 % OTUs of the total OTUs, which was a very small proportion compared with other reports [29]. The second predominant phylum of Actinobacteria showed an obviously increasing trend with the elevated application of N fertilizer.…”
Section: Bacterial Community Compositioncontrasting
confidence: 60%
“…After hydrocarbon pollution, bacteria from several genera, including Gordonia and Rhodococcus (Actinobacteria), Sphingomonas, Acinetobacter, and Pseudomonas (Proteobacteria), and Bacillus and Exiguobacterium (Firmicutes) are usually enriched (5)(6)(7)(8). However, the magnitude and dynamics of microbial community shifts are dependent on the environment (e.g., soil type, freshwater, and seawater), pollution time, hydrocarbon composition (e.g., different crude distillates and specific hydrocarbon), and remediation treatment (9)(10)(11)(12).…”
mentioning
confidence: 99%
“…This observation contradicts many previous investigations in which Proteobacteria were frequently identified as the most abundant phylum in oil-contaminated environments. For instance, Proteobacteria was identified as the most dominant phylum in Algerian oilfield injection waters (Lenchi et al 2013), an oilcontaminated mangrove (Dos Santos et al 2011), and permafrost soils along the China-Russia crude oil pipeline (Yang et al 2012). In this study, Proteobacteria exhibited a relatively low relative abundance in some samples, including sites CQ5, JS1, JS2, JS4, XJ6, and XJ7.…”
Section: Microbial Community Compositionmentioning
confidence: 58%
“…Bacterial communities were also investigated in permafrost soils along the China-Russia crude oil pipeline by pyrosequencing. The results revealed an immensely higher microbial diversity than anticipated (Yang et al 2012). These pyrosequencing-based studies demonstrated that highthroughput sequencing provide a more complete picture of indigenous microbial communities than traditional molecular techniques.…”
Section: Introductionmentioning
confidence: 73%